Prevalence of intestinal metaplasia, dysplasia, and esophageal adenocarcinoma in patients with irregular Z-line: a systematic review and meta-analysis - Vishali Moond; Pradeep Yarra; Mannat Bhatia; Sheza Malik; Vineel Malavarappu; Hassam Ali; Saurabh Chandan; Douglas G. Adler; Babu P. Mohan (Clinical Endoscopy)
Background/Aims The irregular Z-line, defined as a segment of columnar mucosa less than 1 cm in the distal esophagus, is often biopsied despite guidelines advising against it due to a low risk of progression to esophageal adenocarcinoma (EAC). However, the clinical significance of an irregular Z-line remains unclear. This meta-analysis examines the prevalence of Barrett’s esophagus, dysplasia, and EAC in patients with an irregular Z-line. Methods We searched Medline, Embase, and Scopus databases up to October 2023 for studies on the prevalence of Barrett’s esophagus, dysplasia, and EAC in these patients. A random-effects model was used for meta-analysis, and heterogeneity was assessed using I2 statistics. Results Nine studies involving 17,637 patients were analyzed. Among those with an irregular Z-line, the prevalence of intestinal metaplasia was 29.4%. In patients with intestinal metaplasia, dysplasia was found in 6.2%, low-grade dysplasia in 5.9%, high-grade dysplasia in 1.6%, and EAC in 1.5%. These rates were higher compared to those without intestinal metaplasia. Conclusions Patients with an irregular Z-line and intestinal metaplasia may be at higher risk and could benefit from endoscopic surveillance. Further studies are needed to determine the necessity of biopsying irregular Z-lines.